Islamic Values and Local Wisdom in Contemporary Cultural Tourism at the Temple - Suheri Harahap; Nurman Achmad; Afwan Syahril Manurung (MASI Mandiri Edukasi, 2026)
The existence of non-Islamic cultural heritage sites within predominantly Muslim communities often raises questions regarding the interaction between religious identity and cultural tourism management. This study aims to examine how Islamic values and local wisdom contribute to the development of inclusive cultural tourism at the Bahal Temple in Portibi District, North Padang Lawas, without diminishing the religious identity of each group. This research employs a qualitative method with an anthropological approach to religion. Data were collected through in-depth interviews, participant observation, and documentation involving key informants and local community members around the Bahal Temple area. The findings indicate that the local community can harmonize Islamic values with local wisdom in managing cultural tourism. Values such as tolerance (tasamuh), mutual respect, and social harmony are reflected in practices like somang do mulia (respect) and patik dohot pasu-pasu (deliberation), which function as social guidelines in maintaining interreligious harmony. This integration creates an inclusive and sustainable tourism model in which cultural preservation and community cohesion mutually reinforce one another. This study offers a new perspective on cultural tourism development by exploring the synergy between Islamic values and pre-Islamic heritage, demonstrating that religious consciousness can serve as a foundation for inclusive and sustainable tourism practices.